Hip problems and arthroscopy: adolescent hip as it relates to sports - Jacoby, L.; Yi-Meng, Y.; Kocher, M. S. (Clinics in Sports Medicine, 2011)
Injuries of the hip and pelvis in pediatric athletes are receiving increased attention, which may be due, in part, to the increased participation in competitive sports and focusing on a single sport at younger ages. With the advent of hip arthroscopy and the development of more advanced imaging of the hip through magnetic resonance imaging, internal derangements of the hip such as labral tears, loose bodies, femoroacetabular impingement, and chondral injuries are being diagnosed and treated with increased frequency. This article reviews the more common injuries of the hip and pelvis in pediatric athletes.